2018
DOI: 10.4172/clinical-practice.1000409
|View full text |Cite
|
Sign up to set email alerts
|

The patient burden of opioidinduced bowel dysfunction

Abstract: C-reactive protein (CRP) is a blood marker for inflammation and is an independent prognostic factor for many human cancers. Combined with albumin levels, it forms the basis of the Glasgow Index for cancer prognosis. We reviewed the literature on CRP and HCC and also evaluated blood CRP levels and combination CRP plus albumin levels in a large HCC cohort. In order to understand the prognostic significance of CRP, we retrospectively examined a large HCC cohort and examined the relationship of CRP levels to tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…We have recently shown that increased CRP levels are also associated with increased maximum tumor diameter (MTD) in HCC patients [18]. In the present study, we have focused on HCC patients with low AFP and normal AFP levels to examine whether inflammatory markers might also relate to HCC size and possibly have diagnostic usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that increased CRP levels are also associated with increased maximum tumor diameter (MTD) in HCC patients [18]. In the present study, we have focused on HCC patients with low AFP and normal AFP levels to examine whether inflammatory markers might also relate to HCC size and possibly have diagnostic usefulness.…”
Section: Introductionmentioning
confidence: 99%